Esophageal stenting for benign and malignant disease: European Society of Gastrointestinal Endoscopy (ESGE) Clinical Guideline - Spaander, Manon C. W.; Baron, Todd H.; Siersema, Peter D.; Fuccio, Lorenzo; Schumacher, Brigitte; Escorsell, Àngels; Garcia-Pagán, Juan-Carlos; Dumonceau, Jean-Marc; Conio, Massimo; de Ceglie, Antonella; Skowronek, Janusz; Nordsmark, Marianne; Seufferlein, Thomas; Van Gossum, André; Hassan, Cesare; Repici, Alessandro; Bruno, Marco J. (Endoscopy, 2016)
This Guideline is an official statement of the European Society of Gastrointestinal Endoscopy (ESGE), endorsed by the European Society for Radiotherapy and Oncology (ESTRO), the European Society of Digestive Endoscopy (ESDO), and the European Society for Clinical Nutrition and Metabolism (ESPEN). The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system was adopted to define the strength of recommendations and the quality of evidence.Main recommendations for malignant disease1 ESGE recommends placement of partially or fully covered self-expandable metal stents (SEMSs) for palliative treatment of malignant dysphagia over laser therapy, photodynamic therapy, and esophageal bypass (strong recommendation, high quality evidence).2 For patients with longer life expectancy, ESGE recommends brachytherapy as a valid alternative or in addition to stenting in esophageal cancer patients with malignant dysphagia. Brachytherapy may provide a survival advantage and possibly a better quality of life compared to SEMS placement alone. (Strong recommendation, high quality evidence.) 3 ESGE recommends esophageal SEMS placement as the preferred treatment for sealing malignant tracheoesophageal or bronchoesophageal fistula (strong recommendation, low quality evidence).4 ESGE does not recommend the use of concurrent external radiotherapy and esophageal stent treatment. SEMS placement is also not recommended as a bridge to surgery or prior to preoperative chemoradiotherapy. It is associated with a high incidence of adverse events and alternative satisfactory options such as placement of a feeding tube are available. (Strong recommendation, low quality evidence.)Main recommendations for benign disease1 ESGE recommends against the use of self-expandable stents (SEMSs) as first-line therapy for the management of benign esophageal strictures because of the potential for adverse events, the availability of alternative therapies, and costs (strong recommendation, low quality evidence).2 ESGE suggests consideration of temporary placement of SEMSs as therapy for refractory benign esophageal strictures (weak recommendation, moderate evidence). Stents should usually be removed at a maximum of 3 months (strong recommendation, weak quality evidence).3 ESGE suggests that fully covered SEMSs be preferred over partially covered SEMSs for the treatment of refractory benign esophageal strictures, because of their lack of embedment and ease of removability (weak recommendation, low quality evidence). 4 For the removal of partially covered esophageal SEMSs that are embedded, ESGE recommends the stent-in-stent technique (strong recommendation, low quality evidence).5 ESGE recommends that temporary stent placement can be considered for treating esophageal leaks, fistulas, and perforations. The optimal stenting duration remains unclear and should be individualized. (Strong recommendation, low quality evidence.)6 ESGE recommends placement of a SEMS for the treatment of esophageal variceal bleeding refractory to medical, endoscopic, and/or radiological therapy, or as initial therapy for patients with massive esophageal variceal bleeding (strong recommendation, moderate quality evidence).